2018
DOI: 10.1093/infdis/jiy139
|View full text |Cite
|
Sign up to set email alerts
|

A Microneedle Patch for Measles and Rubella Vaccination Is Immunogenic and Protective in Infant Rhesus Macaques

Abstract: These results show, for the first time, that MR vaccine delivered by MN patch generated protective titers of neutralizing antibodies to both measles and rubella in infant rhesus macaques and afforded complete protection from measles virus challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Similar studies on influenza vaccination have demonstrated comparable or superior responses when compared to responses from conventional intramuscular vaccination (Van Damme et al 2009;Kenney et al 2004). Other studies have demonstrated effective levels of neutralizing antibodies in 100% of measles vaccinated non-human primates compared to 75% of subcutaneously vaccinated non-human primates (Joyce et al 2018). In a phase I, partly blinded controlled trial, authors found no significant statistical difference in antibody titers among groups vaccinated with healthcare-administered intramuscular hypodermic needle influenza vaccine, healthcare-administered MN influenza vaccination patch, and self-administered MN influenzavaccination patch, suggesting a possible future for selfadministered vaccines (Rouphael et al 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Similar studies on influenza vaccination have demonstrated comparable or superior responses when compared to responses from conventional intramuscular vaccination (Van Damme et al 2009;Kenney et al 2004). Other studies have demonstrated effective levels of neutralizing antibodies in 100% of measles vaccinated non-human primates compared to 75% of subcutaneously vaccinated non-human primates (Joyce et al 2018). In a phase I, partly blinded controlled trial, authors found no significant statistical difference in antibody titers among groups vaccinated with healthcare-administered intramuscular hypodermic needle influenza vaccine, healthcare-administered MN influenza vaccination patch, and self-administered MN influenzavaccination patch, suggesting a possible future for selfadministered vaccines (Rouphael et al 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Coated and dissolvable MNs represent dry formulations, which compared to liquid‐based injectable vaccines are easier to store, require lesser space and weight capacity for storage, and have reduced cost of transport. Such designs have been developed for viruses including influenza, hepatitis B, hepatitis C, polio, herpes simplex, human papillomavirus, rotavirus, measles and rubella, rabies, HIV, Ebola, chikungunya, and West Nile virus . However despite extensive advances in MN‐based vaccines, there are limited studies addressing the delivery of LAVs.…”
Section: Resultsmentioning
confidence: 99%
“…Only measles and rubella have been successfully adapted for live virus vaccination using MN. Studies involved the intradermal delivery of virus from solid coated or dissolvable MN . With formulation as dissolvable MN vaccine arrays, live measles could be stabilized at 25 °C for months and was demonstrated to induce protective immunity in macaques .…”
Section: Resultsmentioning
confidence: 99%
“…Dissolvable microneedle patches (dMNPs) were fabricated as described previously. 39,40 In this study, the adjuvant-free HBsAg vaccine was mixed into a casting solution at a 60:40 ratio with casting solution containing 25% w/v trehalose and 2.5% w/v CMC in PBS. Failure forces of dMNPs under an axial load were measured utilizing a digital force gauge (MARK-10 Series 5, Copiague, NY).…”
Section: Dissolvable Microneedle Patchesmentioning
confidence: 99%
“…Because infants have weaker immune systems than adults, 50 additional studies will be needed to assess HBsAg vaccination by dMNP in infants, as was done in a recent study of measles and rubella vaccination by dMNP in infant rhesus macaques. 40…”
Section: Immune Response To Adjuvant-free Hbsag Vaccine Delivery Usmentioning
confidence: 99%